Incidence of tarsonemid mites on Cocos nucifera L. (Arecaceae) from Oman with description of a new species of Nasutitarsonemus Beer and Nucifora (Acari: Tarsonemidae) - Lofego, A. C. [UNESP]; Hountondji, F. C. C.; Al-Shanfari, A.; de Moraes, G. J. (Taylor & Francis Ltd, 2011)
Coconut is an important crop grown in the coastal plain of the Dhofar region, south-eastern Oman, on the edge of the Arabian Peninsula desert. It holds a particular place in the landscaping of the region and is also of great interest for the production of coconut drinking water. One of the main pests of coconut in this region is the coconut mite (Aceria guerreronis Keifer). In surveys conducted to understand the dynamics of that mite and its association with other arthropods, the incidence of tarsonemid mites was determined. Steneotarsonemus furcatus de Leon was the most commonly found tarsonemid on fruits as well as on growing tips of coconut seedlings, always at low levels. A few representatives of an undescribed tarsonemid species were also found. That new species is here described as Nasutitarsonemus omani Lofego and Moraes, sp. nov. A key to the species of this little-known genus is provided.
Keywords: Aceria guerreronis; coconut mite; Nasutitarsonemus omani; Steneotarsonemus furcatus